Characterization of the nuclear protein import mechanism using Ran mutants with altered nucleotide binding specificities. - Weis, K (1996)
The small nuclear GTP binding protein Ran is required for transport of nuclear proteins through the nuclear pore complex (NPC). Although it is known that GTP hydrolysis by Ran is essential for this reaction, it has been unclear whether additional energy-consuming steps are also required. To uncouple the energy requirements for Ran from other nucleoside triphosphatases, we constructed a mutant derivative of Ran that has an altered nucleotide specificity from GTP to xanthosine 5' triphosphate. Using this Ran mutant, we demonstrate that nucleotide hydrolysis by Ran is sufficient to promote efficient nuclear protein import in vitro. Under these conditions, protein import could no longer be inhibited with non-hydrolysable nucleotide analogues, indicating that no Ran-independent energy-requiring steps are essential for the protein translocation reaction through the NPC. We further provide evidence that nuclear protein import requires Ran in the GDP form in the cytoplasm. This suggests that a coordinated exchange reaction from Ran-GDP to Ran-GTP at the pore is necessary for translocation into the nucleus.